037 Drug eluting stents (DES) offer benefit over bare metal stents (BMS) inserted during vein graft PCI. (16th May 2012) - Guttmann, O P; Jones, D; Rathod, K; Weerackody, R; Jain, A; Knight, C; Mathur, A; Wragg, A
Abstract : Background: Research trials have shown improved short-term outcome with DES over BMS in Saphenous vein graft (SVG) PCI, primarily by reducing target vessel revascularisation (TVR) for in-Stent Restenosis (ISR). Because of the high event rates in these patients it is not clear if these benefits are maintained long term. We compared the outcomes in patients undergoing SVG stent implantation treated with DES or BMS, over a prolonged follow-up period. Methods: Clinical information was analysed from a prospective database on 512 patients who underwent PCI for SVG lesions between 2003 and 2010 at a London centre. Information was entered at the time of procedure and outcome assessed by all-cause mortality information provided by the Office of National Statistics via the BCIS/CCAD national audit. The primary end point used was major adverse cardiac events (MACE), defined as death, myocardial infarction (MI), stroke and target vessel revascularisation (TVR). Results: There were 293 patients who underwent PCI with BMS and 219 treated with DES. The mean follow-up period was 1086±418 days for the BMS group and 1046±390 days for the DES group. Baseline characteristics were the same between the groups other than diabetes, which was more common in the DES treated group (24% vs 15%, p<0.0001). Per lesion there was a smaller average stent width used in the DES group (3.2±0.05 mm vs 3.7±0.06 mm, p=0.0001) however, there was no significant difference between the stent length (20.1±0.60 mm vs 19.0±0.54 mm, p=0.20) or number of stents used (1.66 vs 1.68, p=0.56). There was similar use of distal protection devices (39.2% vs 48.3%, p=0.08) and procedural success (93.7% vs 93.0%, p=0.78) in the two groups. There was a significant difference in MACE between the two groups in favour of DES (30.2% BMS vs 18.9% DES group [p=0.04] over the 5-year follow-up. MACE was driven by in-stent restenosis in both groups and the difference between groups was due to increased TVR in the BMS group. There was no difference in death, MI or stroke between the stent types. Age-adjusted Cox analysis showed an decrease in the hazard of events for DES compared to BMS (HR 0.60, 95% CIs 0.03 to 0.69) and this was maintained with multiple adjustment (HR 0.52, 95% CIs 0.05 to 0.89). Conclusions: In our cohort of patients who had PCI for treatment of SVG disease the use of DES resulted in lower MACE rate compared to BMS over a 5-year follow-up.